MicroRNA Regulatory Network: Structure and Function - Liu, Zengrong (Springer Netherlands, 2018)
This book discusses topics related to the topological structure and biological function of gene networks regulated by microRNAs. It focuses on analyzing the relation between topological structure and biological function, applying these theoretical results to gene networks involving microRNA, illustrating their biological mechanisms, and identifying the roles of microRNA in controlling various phenomena emerging from the networks. In addition, the book explains how to control the complex biological phenomena using mathematical tools and offers a new perspective on studying microRNA. It is a useful resource for graduate students and researchers who are working on or interested in microRNAs and gene network.